Non-nuclear predicates in Mazahua (oto-manguean) - Mora-Bustos, Armando (2022)
The present research describes non-nuclear predicates that modify the nucleus of the matrix clause, the clause or its constituents. The non-nuclear predicates show grammatical properties of their own. In order to make this explicit, data from the Mazahua language are presented in order to warn that these are not complex constructions, but simply modifiers, considering that the language presents any grammatical category as the nucleus of the predicate. From the set of non-nuclear clauses, it is proposed that they can be realized as coverbs, operators, adverbial property predicates, adverbial temporal predicates and juxtaposed direction predicates. The research concludes that non-nuclear predicates are neutralized in person and time, lack argumentative structure, have no internal modifiers, belong to a closed class, acquire specific positions, maintain a juxtaposition relation and perform modifications similar to the adverb. In this respect, modification must be understood in syntactic and semantic terms, that is, a relation of structural dependence between a nucleus and the units that are under a status of dependence, dominance or subordination; while semantically, they restrict and make explicit the reference of the modified grammatical unit, as well as the features that denote specific properties of the modified.